Forced migration: evidence and policy challenges. (15th September 2022) - Quinn, Simon; Ruiz, Isabel
Abstract: This paper presents a summary assessment of this issue of the Oxford Review of Economic Policy, on forced migration. The issue is concerned with four important questions: (i) What are the general mechanisms by which forced migrants should be managed, and what frameworks should be used for supporting them? (ii) How can policy help refugees integrate into host economies; and what are the likely consequences of this integration? (iii) How are host communities likely to respond to the influx of refugees, and how can policy help to smooth this transition? and (iv) What role can policy play to encourage resilience among refugees and internally displaced people—and, one day, potentially support their return? Drawing from a diverse set of experiences and country case studies, the invited authors—who range from academics to policy practitioners—present and discuss current evidence and draw from their expertise to offer insights on these general themes in the economic policy response to forced migration. Among others, some of the recurring ideas for the design of policy include the need of anticipatory, systematic, and long- term approaches to the 'management' of forced displacement; the importance of building evidence, quantifying impacts, and understanding the distributional consequences of forced migration; and finally, the importance of bridging a gap in how the evidence is communicated and understood in the broader community.